Soil pipe flow tracer experiments: 2. Application of a streamflow transient storage zone model. Issue 8 (21st November 2015) - Zhou, Yan; Wilson, G. V.; Fox, G.A.; Rigby, J.R.; Dabney, S.M.
Abstract: Soil pipes are important subsurface flow pathways in many soil erosion phenomena. However, limited research has been performed on quantifying and characterizing their flow and transport characteristics. The objectives of this research were to determine the applicability of a streamflow model with transient storage in deriving flow and transport characteristics of soil pipes. Tracer data from pulse inputs were collected in four different soil pipes after a fluorescein dye was injected in the upstream end of each soil pipe network in three branches (west, middle, and east) of a main catchment and a back catchment in Goodwin Creek Experimental Watershed in Mississippi. Multiple sampling stations were positioned along each soil pipe network. The transient storage zone model OTIS‐P was executed inversely to estimate transport parameters by soil pipe reach such as the soil pipe cross‐sectional area ( A ), soil storage zone cross‐sectional area ( As ), and exchange rate between the soil pipe and the soil storage zone ( αs ). Model convergence was achieved, and simulated breakthrough curves of the reaches were in good agreement with actual tracer data for eight of the nine reaches of the three branches of the Main Catchment and five of the seven reaches of the Back Catchment soil pipe. Simulation parameters for the soil pipe networks were similar to the range of values reported for flow and transport characteristics commonly observed in streams. Inversely, estimated soil pipe flow velocities were higher with increased tortuosity, which led to a smaller cross‐sectional areas predicted for the soil pipe flowpaths, while other parameters were not sensitive to tortuosity. In general, application of One‐Dimensional Transport with Inflow and Storage‐P to this unique soil pipe condition suggested larger transient storage ( As and αs ) compared with most stream systems. This was hypothesized to be because of relatively higher ratio of the wetted perimeter to flow area in the soil pipe, the hydraulic roughness of the soil pipe, potential retention in collapsed portions of the pipe, and interaction with smaller preferential flow systems. Copyright © 2015 John Wiley & Sons, Ltd.